Modeling the Monthly Average of the Quota Values per AFP and Type 2 Fund with the Box and Jenkins or ARIMA Methodology - Bazán Ramírez, Wilfredo (2021)
The economic and financial crises in the world are recurrent due to the presentation of different patterns. These crises have affected the returns of the private pension system in Peru and there were no effective responses from the Pension Fund Administrators (AFPs). By using the Box and Jenkins or Autoregressive Integrated Moving Average (ARIMA) methodology, the behavior of the monthly average returns of the daily quota values of the type 2 fund—which began in December 2005—of each AFP can be described and forecast. Type 2 funds are distributed 55% in fixed income and 45% in equities, with a balanced profile destined for workers between 45 and 60 years old. The data type of the monthly average returns of the type 2 fund corresponds to the weak stationary time series, since the first moments such as the mean and the variance and autocovariance are time‑invariant.